Investigation of InAlN Layers Surface Reactivity after Thermal Annealings: A Complete XPS Study for HEMT. (1st January 2018) - Bourlier, Y.; Bouttemy, M.; Patard, Olivier; Gamarra, Piero; Piotrowicz, S.; Vigneron, J.; Aubry, R.; Delage, S.; Etcheberry, A.
Abstract : The surface chemistry of InAlN ultra-thin layers, having undergone an oxidation procedure usually running through the HEMT fabrication process (850°C, O2 and O2 +Ar) is studied by XPS. The suitability of XPS analysis to operate as a retro-engineering tool for added value microelectronic devices fabrication is shown. A precise examination of the Al2p, In3d5/2, N1s, and O1s peaks directly informs about spatial and atomic arrangement. The formation of a covering 3 nm surface oxide is evidenced after O2 annealing. Once annealed, two specific additional N1s contributions are shown, at higher (404.0 eV) and lower binding energies (397.4 eV) compared to the InAlN matrix one (396.5 eV). To our knowledge, such fingerprint is rather unusual for ternary III-V materials. It reveals the formation of a nitrogen deficient interlayer, situated between the oxide overlayer and the undisturbed matrix, and the presence of interstitial N2 molecules trapped at the interface. After Ar annealing, both oxide and interface layers are partially reorganized. InAlN reactivity toward higher annealing temperature (950°C) and its stability over time is finally discussed. N2 molecules are unstable and progressively eliminated in time although nitrogen deficient interlayer still remains. Thermal treatments below 850°C are recommended to preserve the barrier chemical integrity.